A comparative study of two-equation turbulence models for simulating microscale wind flow. (1st January 2000) - Ehrhard, J.; Kunz, R.; Moussiopoulos, N.
Numerical modelling of turbulence plays a crucial role in providing accurate microscale wind fields which are necessary to predict transport and dispersion of pollutants in the vicinity of buildings reliably. Although more elaborate turbulence models have been developed, two-equation turbulence models are widely applied in atmospheric flow and dispersion models. The large CPU time required for direct numerical simulation (DNS) and large eddy simulation (LES) still prohibits their application to microscale wind flow simulations of practical interest. In this study, the results obtained by the microscale model MIMO for the three-dimensional flow around a surface mounted cubical obstacle, using different two-equation turbulence models, are discussed. The accuracy of the investigated turbulence models is assessed by comparing the numerical results with wind tunnel measurements.